Numerical Studies of the Effects of the Substrate Structure on the Residual Stress in Laser Directed Energy Additive Manufacturing of Thin-Walled Products - Hang Jing; Peng Ge; Zhao Zhang; Jun-Qi Chen; Zhong-Ming Liu; Wei-Wei Liu (Metals, 2022)
A new method of controlling the residual stress in laser directed energy deposition additive manufacturing (DED AM) products proposed based on constraints used in manufacturing and the substrate design. The simulation results of the residual stress, which were validated with the experimental measured data, showed that weaker constraints on the substrate could greatly decrease the residual stress in the laser DED AM products. In addition, by designing local reduced thickness regions into the substrate, such as long strip holes or support legs, the residual stress in DED AM products could be further decreased. In this study, when long strip holes were designed in the substrate, the tensile residual stress was decreased by 28%. An even smaller amount of residual stress was achieved when the design structure was changed to support legs. The tensile residual stress decreased by more than 30%. The fewer support legs, the smaller the residual stress. The residual stress in DED AM products could be well-controlled by design, while the stiffness can be weakened with fewer constraints.